Shorthand notation for lipid structures derived from mass spectrometry - Liebisch, Gerhard; Vizcaíno, Juan Antonio; Köfeler, Harald; Trötzmüller, Martin; Griffiths, William J; Schmitz, Gerd; Spener, Friedrich; Wakelam, Michael J O (Journal of lipid research, 2013)
There is a need for a standardized, practical annotation for structures of lipid species derived from mass spectrometric approaches; i.e., for high-throughput data obtained from instruments operating in either high- or low-resolution modes. This proposal is based on common, officially accepted terms and builds upon the LIPID MAPS terminology. It aims to add defined levels of information below the LIPID MAPS nomenclature, as detailed chemical structures, including stereochemistry, are usually not automatically provided by mass spectrometric analysis. To this end, rules for lipid species annotation were developed that reflect the structural information derived from the analysis. For example, commonly used head group-specific analysis of glycerophospholipids (GP) by low-resolution instruments is neither capable of differentiating the fatty acids linked to the glycerol backbone nor able to define their bond type (ester, alkyl-, or alk-1-enyl-ether). This and other missing structural information is covered by the proposed shorthand notation presented here. Beyond GPs, we provide shorthand notation for fatty acids/acyls (FA), glycerolipids (GL), sphingolipids (SP), and sterols (ST). In summary, this defined shorthand nomenclature provides a standard methodology for reporting lipid species from mass spectrometric analysis and for constructing databases.